(untitled) (Journal of Accessibility and Design for All, 2023)
This study investigates strategies for developing visual sensory-based quiet rooms for individuals with autism spectrum disorders to reduce maladaptive behaviours and emotions. Optimizing visual sensory comfort in a quiet room is expected to help a person relieve the maladaptive behaviours and emotions that he/she is experiencing. This laboratory-based case study was conducted through a literature review and case studies in two quiet rooms in a school as the laboratory observation. Both schools provide special education services and an inclusive education school. This study aims to provide a reference for creating spaces for autistic individuals in supporting a more inclusive and sustainable environment. A total of eight respondents (four students from each school), aged between 7-21 years old, were involved in this study. Data for the analysis was obtained by observing the physical conditions of the existing quiet room and assessing the respondents’ behaviour and emotions while they were inside the room. The behaviour and emotion assessments were based on 12 active behaviours and emotions on the Aberrant Behavior Checklist - Irritability (ABC-I) instrument. Meanwhile, lighting simulations were also conducted using the software DIALux evo 8.1 to determine the rooms’ lighting situation. The case studies showed that (1) most of the respondents showed response related to the quiet room’s visual comfort; (2) the respondents in a quiet room with less lighting contrast intensity were more likely to experience a decrease in maladaptive behaviour and emotion; and (3) one of the respondents gave more response in auditory stimulation, which showed that non-visual sensory stimulation should also be put into consideration for a quiet room design. It was concluded that visual stimulation in a quiet room might affect the users’ maladaptive behaviour or emotional change. Therefore, a visual-sensory-based intervention for a quiet room potentially increases its effectiveness.